Santhal 'Pot' and songs on Netajee Subhas Bose, leader of the Freedom Struggle of India. Recorded by Shahriar Kabir in Barasat, West Bengal at a handicraft fair on 29/01/2000 - Kabir, Shahriar.
Santhal 'Pot' and songs on Netajee Subhas Bose, leader of the Freedom Struggle of India. Recorded by Shahriar Kabir in Barasat, West Bengal at a handicraft fair on 29/01/2000.